The high expression of miR-564 in patients with systemic lupus erythematosus promotes differentiation and maturation of DC cells by negatively regulating TP53 expression in vitro. (August 2021) - Teng, Ziyue; Lin, Xiaoying; Luan, Chunyan; Sun, Yixuan; Li, Xiaolan
Background: miRNA is involved in the occurrence and progression of systemic lupus erythematosus (SLE), but the regulatory effect of miRNA on dendritic cells in SLE patients is still unclear. Material and methods: Bioinformatics methods were used to analyze the differentially expressed miRNA and its target genes in SLE patients. In vitro experiments were conducted to explore the effects and mechanisms of differentially expressed miRNAs in SLE patients on the differentiation and maturation of monocyte-derived dendritic cells. Results: Bioinformatics analysis showed that miR-564 was up-regulated in SLE patients, and TP53 was the core target gene of miR-564. The expression level of miR-564 showed a rising trend during the differentiation and maturation of monocytes into Mo-DC cells. The differentiation, maturation and proliferation of Mo-DC cells were significantly inhibited by transfection with miR-564 antagomir. The expression of TP53 is negatively regulated by miR-564. In rescue experiments, the proliferation and migration of DC cells were significantly restored by co-transfection of miR-564 antagomir and TP53 si-RNA. Conclusion: Highly expressed miR-564 promotes the maturation, proliferation of Mo-DC cells by negatively regulating the expression of TP53.